The Buffering Effect of Machiavellianism on the Relationship Between Role Conflict and Counterproductive Work Behavior - Zhao, Jun; Xiao, Sufang; Mao, Jianghua; Liu, Wenxing (Frontiers in Psychology, 2018)
Considering the destructive effects of counterproductive work behavior (CWB) in the workplace, scholars have put much effort into revealing its antecedents. The purpose of this paper is to examine how Machiavellianism helps mitigate the effect of role conflict on CWB in China. Using data collected from three phases, this research revealed that role conflict had a positive effect on CWB via emotional exhaustion. Machiavellianism moderated the relationship between role conflict and emotional exhaustion, such that this relationship got weaker for employees with higher Machiavellianism. Furthermore, Machiavellianism moderated the relationship between role conflict and CWB via emotional exhaustion, as such, it became weaker for employees with high Machiavellianism.